ANTIBACTERIAL AND ANTI-INFLAMMATORY ACTIVITIES OF CRUDE EXTRACTS OF THREE TOGOLESE MEDICINAL PLANTS AGAINST ESBL KLEBSIELLA PNEUMONIAE STRAINS - Toudji, Gerard A.; Thiombiano, Emmanuel; Karou, Simplice D.; Anani, Kokou; Adjrah, Yao; Gbekley, Holaly E; Kiendrebeogo, Martin; Ameyapoh, Yaovi; Simpore, Jacques (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Pithecellobium dulce (Roxb.) Benth., Securidaca longepedunculata Fresn and Cryptolepis sanguinolenta (Lindl.) Schlt are three plants widely used in the Togolese traditional medicine to treat microbial infections. Some studies reported their antibacterial activity alone but until know there no data concerning their possible interaction with conventional antibiotics. The main objective of this study was to investigate the antibacterial activity of the association of the crude extracts of the three plants with some conventional antibiotics. We further evaluate the antioxidant and the anti-inflammatory activities of the extracts on rat’s model.Materials and methods:The antimicrobial activity was evaluated by the broth microdilution assay and the Fractional inhibitory concentrations (FIC) determined by the checkerboard method. The anti-inflammatory activity was evaluated using the Carrageenan- induced rat paw edema model. The antioxidant activities and the phenol contents were determined by spectrophotometry.Results: The MICs of hydroethanolic extract of plants ranged from 3.125 to 100 mg/mL on Klebsiella pneumoniae strains. Synergistic action was observed only with the combination of Imipenem/P. dulce, imipenem/C. sanguinolenta, amikacin/P. dulce and amikacin/C. sanguinolenta against the ESBL negative Klebsiella pneumoniae strain. Of the 21 associations, 15 were antagonistic on the ESBL-producing strains. The indifference effect was observed with the combination of the extract of Securidaca longepedunculata and the following antibiotics imipenem, amikacin, tetracyclin, ciprofloxacin, Cefotaxim; and Sulfametoxazol+Trimethoprim. The in vitro anti-inflammatory with Lipoxygenase inhibition activity was best with C. sanguinolenta extract while the in vivo paw edema model revealed that S. longepedunculata was the highest reducer of paw edema. In addition white blood cells count and biochemical parameters such as total proteins and immunoglobulins were significantly affected by the administration of plant extracts.Conclusion: This study revealed that the three plants although they may inhibit the bacterial growth by themselves, but there is also a possible synergistic action with the commercial antibiotics. Further investigations are needed to identify the active compounds and their mechanism of action.